Personal Tragedy or System Failure: A Qualitative Analysis of Narratives of Caregivers of People with Severe Mental Illness in Hong Kong and Taiwan - Chiu, Marcus Yu-Lung; Wei, Grace Fang-Wan; Lee, Sing (International journal of social psychiatry, 2006)
Background: Most studies agree that mental illness brings a heavy objective and subjective burden of care on the family and especially the caregivers. However, very little attention has been paid to the wider context in which this burden is shaped and sustained. Material: In-depth interviews were conducted with 11 caregivers in Hong Kong and Taiwan and subsequent analysis identified four major themes: mystical knowledge beyond understanding, persistent self-blame and lay explanation, inertia of caregivers and non-responsive service system, and unsatisfying encounters with medical staff. Discussion: The results of the study indicate that these families did not get the services they needed. In spite of recounting many system failures, most respondents attributed their situation to tragedy and misfortune at personal and family levels. Such a discourse is closely connected to a wider context of health and social care. The Hong Kong subjects complained more, felt more helpless, and had more persistent self-blame and lay explanation than the Taiwanese subjects. Conclusions: To reduce such experiences, this paper calls for inclusive policies for the family, new education strategies and reflections on the roles of mental health professionals in empowerment and advocacy beyond conventional treatment, counseling and education.